2012
DOI: 10.5455/msm.2012.24.68-72
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Polypharmacy and Drug Interaction Among Hospitalized Patients: Opportunities and Responsabilities in Pharmaceutical Care

Abstract: Goal:Polypharmacy and drug-related problems (DRPs) have been shown to prevail in hospitalized patients. We evaluated the prevalence of polypharmacy; and investigated relationship between polypharmacy and: symptoms of DRPs, number of drugs and OTC, index of cumulative morbidity, length of exposure to polypharmacy and the number of days of hospital stay among hospitalized patients.Methodology:A study was performed in Pharmacies „Eufarm Edal“ Tuzla from 2010 to 2011. Polypharmacy was defined as using ≥ 3 drugs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…By 2050, nearly 8 in 10 of the world's older population will be living in the less developed areas [2]. This increase in life expectancy has brought about increased numbers of certain chronic illnesses, which involves hospital admissions, multiple medications and its associated ADR's [3]. Inappropriate use of medicines is one of the challenges of the public health domain and may lead to serious (ADRs) [4]that account for 3% to 23% of hospital admissions, prolong hospital stays, and increase in morbidity and mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…By 2050, nearly 8 in 10 of the world's older population will be living in the less developed areas [2]. This increase in life expectancy has brought about increased numbers of certain chronic illnesses, which involves hospital admissions, multiple medications and its associated ADR's [3]. Inappropriate use of medicines is one of the challenges of the public health domain and may lead to serious (ADRs) [4]that account for 3% to 23% of hospital admissions, prolong hospital stays, and increase in morbidity and mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 2-3 decades, global health care is facing prominent issues associated with age, comorbidities and polypharmacy. On literature survey related to polypharmacy and its consequences among elderly, it is observed that most of the researches addressed western population (Maher et al, 2014;Nobili et al, 2011;Trumic et al, 2012). Even though few researchers studied polypharmacy among geriatrics in Indian population, the consequences and contributing factors associated with polypharmacy were addressed only in few studies.…”
Section: Introductionmentioning
confidence: 99%
“…The neurological effects described for acrylamide for single oral doses are in the range of 126 mg/kg in rats and rabbits and 100 mg/kg in dogs [4]. In a low-level occupational setting subchronic exposure the prominent neurotoxic effects found for acrylamide include numbness of hands and feet, skeletal muscle weakness and ataxia, and in an experimental setting acrylamide intoxication consisted of neurogenic autonomic dysfunction such as urinary retention, impaired vasomotor control and baroreceptor dysfunction [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a low-level occupational setting subchronic exposure the prominent neurotoxic effects found for acrylamide include numbness of hands and feet, skeletal muscle weakness and ataxia, and in an experimental setting acrylamide intoxication consisted of neurogenic autonomic dysfunction such as urinary retention, impaired vasomotor control and baroreceptor dysfunction [9]. Some other studies concluded in order to obtain clinical effect lower doses need to accumulate [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation